Effects of dietary non-viable Bacillus sp. SJ-10, Lactobacillus plantarum, and their combination on growth, humoral and cellular immunity, and streptococcosis resistance in olive flounder (Paralichthys olivaceus). (August 2020) - Nguafack, Tankeng Terence; Jang, Won Je; Hasan, Md Tawheed; Choi, Youn Hee; Bai, Sungchul C.; Lee, Eun-Woo; Lee, Bong-Joo; Hur, Sang Woo; Lee, Seunghyung; Kong, In-Soo
Abstract: Heat-killed (HK) Bacillus sp. SJ-10 (B), HK Lactobacillus plantarum (P), and their combination were dietary supplemented to olive flounder ( Paralichthys olivaceus ) to quantify the effects on growth, innate immunity, and disease resistance. Four test diets were supplied: a control feed free of HK probiotics, 1 × 10 8 CFUs g –1 single treatments of each of HK B (HKB) and HK P (HKP), and an equal proportion of (0.5 HKB + 0.5 HKP) × 10 8 CFUs g –1 (HKB0.5 HKP0.5 ). At 8 weeks of completion feeding trail, HKB0.5 HKP0.5 significantly (P < .05) improved growth, feed utilization, and nonspecific immune parameters (respiratory burst and superoxide dismutase) compared to the control group. Similarly, serum lysozyme and myeloperoxidase activities were higher in both HKB and HKB0.5 HKP0.5 groups. The levels of pro-inflammatory cytokine IL-6 in the liver and IL-1β in the liver, kidney, and spleen were also improved in the treatments, but microvilli length was only increased in HKB0.5 HKP0.5 . After Streptococcus iniae 1 × 10 8 CFUs mL −1 challenged; HKB and HKB0.5 HKP0.5 had a higher survival than control and HKP. Overall, dietary administration of synergy HK probiotics elevated growth, cellular and humoral immunity, and streptococcosis resistance in olive flounder. Highlights: Heat killed probiotic mixture (HKB0.5 HKP0.5 ) was fed to the olive flounder. HKB0.5 HKP0.5 produce positive effects on growth and innate immunity. Transcription levels of IL-6 and IL-1β are upregulated by HKB0.5 HKP0.5 . Dietary HKB0.5 HKP0.5 is able to increase microvillus length in the intestine.